The Effectivity Of Public Services Based On Smart Goverment In Bukit Raya Distric Pekanbaru City - Harapan Tua Ricky Freddy; Willya Achmad; Mimin Sundari Nasution (Journal of Governance, 2022)
The Bukit Raya District in Pekanbaru City is the first sub-district to implement one of the pillars, namely E-Government, from the realization of the Pekanbaru City Vision, also known as the Smart City Madani concept. The Bukit Raya District Government of Pekanbaru City, based on Pekanbaru Mayor Regulation Number 56 of 2019, has made a transformation in the form of various public service innovations by utilizing the use of IT technology to facilitate services as one of the indicators of the pillars of smart government (Smart Government) with the vision of working hard, being disciplined, creative, innovative, and having an entrepreneurial spirit and spirit. This is intended to create clean governance and the realization of good governance in order to provide quality, fast, precise, cheap, and good public services. The research problem that will be answered is how effective the transformation of public services based on Smart Government is applied in Bukit Raya District, Pekanbaru City. The theory used refers to the opinion of Bryson (2002) about hexagonal services, which rests on the assumption that services that are considered effective must go through a market test in the Service Management System. The research method used is qualitative with a case study approach. Relevant analysis methods are performance analysis techniques, individual experiences, and institutional behavior (Moeleong, 2006; Bugin, 2011). The results showed that the effectiveness of the transformation of public services based on "Smart-Government" carried out by the Bukit Raya District Government in Pekanbaru City was classified as less effective. This is due to, the service management system factor, which has relatively many application menus and makes it difficult for users; limited human resources in the field of information technology; limited smartphone ownership; data and information that is less continuous and transparent about development programs; and others. In addition, the online-based service designs are not supported by a database of community needs, so that people still feel less satisfied, less fluent, and less able to do business. Research recommendations include simplifying the standard standards of smart-government-based public service systems into one internet website application with a comprehensive menu of applications according to the needs of the community.